(Re)Interpretasi Arsitektur Tropis: Kajian Teoretis tentang Determinasi Arsitektur Vernakular dan Regionalisme - Pandu K. Utomo; Dharwati P. Sari; Rini S. Saptaningtyas (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2021)
In the field of architecture, theory is an important aspect that determines the perspective and direction in achieving goals. The domain of theory of architecture includes the framework of thinking in architectural design process, research, and architectural criticism. In the order of the architectural design, architectural theory even becomes the most important foundation to support the design concept. This research is motivated by the importance of understanding tropical architecture. Implemented by qualitative methods, author examines tropical architecture to find a more comprehensive interpretation than what has been understood so far. This research relies on relevant theories to build a holistic frame of mind, then concludes that there is a close relationship between tropical architecture, vernacular architecture, and regionalism in architecture. The results of this research are expected to be fundamental framework for anyone who wants to endorse tropical architecture as a foundation of thinking, in design and research.